Improvement of thermal conductivity and mechanical properties for polybenzoxazine composites via incorporation of epoxy resin and segregated structure - Wang, Yi; Wu, Wei; Drummer, Dietmar; Liu, Chao; Tomiak, Florian; Schneider, Kevin (Materials Research Express, 2020)
Developing tendency of increasing integration in electronic components filed led to the demand for thermally conductive polymer materials. Forming a segregated structure with thermally conductive fillers in the matrix has been proven to be a promising technique. However, the mechanical properties of the material prepared via this technique are commonly sacrificed because the interaction between fillers and matrix are weak. We present a simple method to improve the mechanical properties while maintaining the segregated structure via the collaboration of epoxy and polybenzoxazine(PBz). The fillers, epoxy resin, and benzoxazine(BOZ) were mixed and then hot pressed under 12 MPa of pressure with a certain heating strategy. The thermal conductivity, density, mechanical properties, morphology, and thermal stability of the composites were investigated. With 25 wt% filler, the value of thermal conductivity coefficient of EP/PBz composites reached 0.811 W mK(-1), while that of PBz composites was 0.762 W mK(-1). The tensile strength of the matrix improved from 58.3 MPa to 99.7 MPa.
CRIS-Team WoS Importer:2020-10-02